Computest for window microcomputer testing system. (San Diego, CA Chariot Software Group, 1994)
An instructor's productivity tool that generates tests and answer keys according to specifications the user provides. Users can construct their own tests, and also modify the question bank and test bank provided.
Keywords: Examinations -- Software